Mutagenicity and oxidative damage induced by an organic extract of the particulate emissions from a simulation of the deepwater horizon surface oil burns. (April 2017) - DeMarini, David M.; Warren, Sarah H.; Lavrich, Katelyn; Flen, Alexis; Aurell, Johanna; Mitchell, William; Greenwell, Dale; Preston, William; Schmid, Judith E.; Linak, William P.; Hays, Michael D.; Samet, James M.; et al.
Abstract : Emissions from oil fires associated with the "Deepwater Horizon" explosion and oil discharge that began on April 20, 2010 in the Gulf of Mexico were analyzed chemically to only a limited extent at the time but were shown to induce oxidative damage in vitro and in mice. To extend this work, we burned oil floating on sea water and performed extensive chemical analyses of the emissions (Gullett et al., Marine Pollut Bull, in press, 2017 ). Here, we examine the ability of a dichloromethane extract of the particulate material with an aerodynamic size ≤ 2.5 µm (PM2.5 ) from those emissions to induce oxidative damage in human lung cells in vitro and mutagenicity in 6 strains of Salmonella. The extract had a percentage of extractable organic material (EOM) of 7.0% and increased expression of the heme oxygenase ( HMOX1 ) gene in BEAS‐2B cells after exposure for 4 hr at 20 µg of EOM/ml. However, the extract did not alter mitochondrial respiration rate as measured by extracellular flux analysis. The extract was most mutagenic in TA100 +S9, indicative of a role for polycyclic aromatic hydrocarbons (PAHs), reflective of the high concentrations of PAHs in the emissions (1 g/kg of oil consumed). The extract had a mutagenicity emission factor of 1.8 ± 0.1 × 10 5 revertants/megajoulethermal in TA98 +S9, which was greater than that of diesel exhaust and within an order of magnitude of open burning of wood and plastic. Thus, organics from PM2.5 of burning oil can induce oxidative responses in human airway epithelial cells and are highly mutagenic. Environ. Mol. Mutagen. 58:162–171, 2017. © 2017 Wiley Periodicals, Inc.